(untitled) (Journal of the College of Education for Women, 2019)
Hegel’s book entitled"The science of Beauty" is a serious attempt to establish a foundationfor this science. Hegel decided from the beginning, that his research is limited to artistic beauty more than natural beauty. He regards artistic beauty above the natural beauty as the former is the product of the soul. Everything that comes from the soul is superior to what is found in nature and the worst idea that penetrates human’s thoughtbetter than any product of the nature. Man turned to art as a means of his awareness of his superior soul and his interests. All nations poured their highest outputs of their perceptions in the product of art.